Health care in schoolchildren as a prevention of disease: Health in childhood in the era of COVID-19 - López Ruiz , Manuel José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The study seeks to analyze nutritional statuses in a sample population aged 10 to 12 years after the effects of COVID-19. When measuring BMI, trends towards overweight and obesity are shown in relation to the WHO scales. We found levels of cardiovascular endurance, speed and agility in relation to nutritional statuses. The conclusions corroborate the contributions of the studies and the WHO itself on the care of these health factors as biomarkers of the physical condition of the subjects and of disease prevention.